2022
DOI: 10.1080/0886022x.2022.2033265
|View full text |Cite
|
Sign up to set email alerts
|

Negative anti-phospholipase A2 receptor antibody status at three months predicts remission in primary membranous nephropathy

Abstract: Background The value of anti-phospholipase A2 receptor antibody (anti-PLA2R ab) monitoring at 3 months after diagnosis in membranous nephropathy (MN) remains uncertain. Methods We retrospectively examined the outcome on 1 August 2020 of 59 adult patients (age 54 (44, 68) years, 69% male, SCr 1.0 (0.9, 1.3) mg/dL) diagnosed with MN (kidney biopsy, positive serum anti-PLA2R ab). The outcomes were: kidney survival; partial and/or complete remission. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
8
1
Order By: Relevance
“…The hypercoagulable state due to nephrotic syndrome is not well understood and is probably multifactorial [ 17 ]. The most frequent reported abnormalities include reduced levels of natural anticoagulants such as antithrombin III, plasminogen, and protein C and S (due to urinary losses), increased platelet activation, hyperfibrinogenemia, inhibition of plasminogen activation, and the presence of high-molecular-weight fibrinogen in the serum (due to increased liver synthesis) [ 17 , 18 , 19 , 20 ]. Moreover, hypovolemia, diuretic therapy, and corticosteroid treatment can additionally increase the thrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…The hypercoagulable state due to nephrotic syndrome is not well understood and is probably multifactorial [ 17 ]. The most frequent reported abnormalities include reduced levels of natural anticoagulants such as antithrombin III, plasminogen, and protein C and S (due to urinary losses), increased platelet activation, hyperfibrinogenemia, inhibition of plasminogen activation, and the presence of high-molecular-weight fibrinogen in the serum (due to increased liver synthesis) [ 17 , 18 , 19 , 20 ]. Moreover, hypovolemia, diuretic therapy, and corticosteroid treatment can additionally increase the thrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies emphasized high titer of anti-PLA2R in serum at diagnosis was related to an increased risk of progressive loss of renal function, the rapid transformation from non-nephrotic-range proteinuria to nephrotic-range proteinuria, and a decreased spontaneous remission rate [ 26–31 ]. While some studies found no correlation between the baseline titer of SAb and remission[ 11 , 32 ]. Our analysis showed the presence of SAb was an independent risk factor for no remission.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of PLA2Rab in patients with PMN has led to great progress in the diagnosis, disease activity, treatment response evaluation, and prognosis of the disease [ 16 , 17 ]. Dynamic measurement of serum PLA2Rab titer could predict treatment response and disease relapse [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%